EFFECT OF INDUCED VARIATION ON NUTRITIONAL COMPOSITION OF Capsicum annuum (L.) - TUNDENO BARDE, DANFULLOH; APPAH, JOSEPH; ISYAKU ALHAJI, ABDULLAHI; MOLTONG YILWA, VICTORIA; MAGAJI, YAKUBU; ANDY, BALA; IBRAHIM GALADIMA, AHMED; CORNELIUS TOCHUKWU, NWANKWO (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The effect of X-ray radiation was examined on the nutritional content of Capsicum annuum L. (Pepper seeds Yolo wonder 254 F1). The seeds were subjected to three different doses of X-ray irradiation (3MGy, 6MGy and 9MGy) to observe variation in the nutritional content of the F2 fruit across the treatments and control. The study aimed at using x-ray irradiation to stimulate variation resulting in improved nutritional content of C. annuum. Randomized Complete Block Design (RCBD) with three replications was laid in a field experiment at research farm of Agronomy Department, Faculty of Agriculture, Federal University of Kashere, Gombe State, during the 2021 raining season. Spectrophotometric method was employed using U-V visible Spectrophotometer, as well as Atomic Absorption Spectrophotometry (AAS) was used to determined mineral content. Proximate compositions were also analyzed using standard method. Data obtained were subjected to Analysis of Variance and DMRT at p <0.05 level of significance. Variation in the concentration of vitamins A, B2, B6, B12, C and ß-Carotene were observed. Vitamin C at the control has 142643 ± 1.00d as the highest concentration, while vitamin B12 has 0.002 ± 1.00a as the lowest concentration across all the treatments. Minerals examined were Mg, Ca, K, Fe and PO42- with K having 181.00 ± 5.66c concentration at zero treatment as the highest and Phosphate recorded 0.04 ± 0.04a at 3MGy as the lowest. Phytochemical has Oxalate with 0.89 ± 0.31b recorded at zero exposure and Phytate 0.01 ± 0.00a at 3MGy recorded as highest and lowest concentration respectively. In proximate compositions, Carbohydrates was obtained with 60.67 ± 1.39c at 9.0MGy exposure as the highest concentration, whereas ether extract has 0.72 ± 0.00a at 3MGy has the lowest concentration among all other compositions. The findings revealed that relative increase in the nutritional content of pepper across the treatments were 0MGy exposure to X-ray irradiation produce higher concentration suggesting a possible recovery of useful variant from lower exposure. Eventually, results of this study, revealed that X-ray irradiation has random effect on the nutritional content of pepper.